Mode and Tempo in Western Classical Music of the Common- Practice Era: My Grandmother Was Largely Right – but No One Knows Why - Vladimir J. Konečni (Empirical Musicology Review, 2009)
The work of Post and Huron (2009) is an example of how the received wisdom in musicology can be fruitfully challenged by simple empirical procedures – in this case demonstrating a counterintuitive, yet strong, relationship between the minor mode and fast tempi in the Romantic era. The fact that the authors’ explanation in terms of the emotional similarities of the minor mode with the Sturm und Drang attributes (other than “sadness”) is not wholly convincing in music-historical terms does not diminish the importance of the finding. However, there is still no resolution of the central psychological conundrum of why the minor mode is generally associated with “sadness.” And it is unclear why the authors drew on speech prosody rather than human emotion-driven and emotion-expressing movement for their tempo observations. There are other aspects of the data that require further exploration. One is the differential distribution of the associations of various tempo markings with mode across the periods of the common-practice era. Another is the 3 : 1 preponderance of allegro over adagio in the authors’ search of 50,000 tracks in the ClassicsOnline.com database and the possibility that this ratio is a partial consequence of the psychological implications of the sonata form that were intuitively understood and used by composers.